2018
DOI: 10.1163/15685306-12341500
|View full text |Cite
|
Sign up to set email alerts
|

Birding, Citizen Science, and Wildlife Conservation in Sociological Perspective

Abstract: Sociological research on wildlife typically looks at how nonhuman animals in the wild are hunted, poached, or captured for entertainment, or how they play a symbolic role in people’s lives. Within sociology, little research exists on how people appreciate nonhuman animals in the wild, and how people contribute to wildlife conservation. I explore birding-related citizen science projects in the US. Citizen science refers to scientific projects carried out by amateurs. Literature on citizen science focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Bushway et al (2011) found younger people who were employed and on lower incomes were more likely to cite time and money as barriers, whereas retirees were the least likely. Our study found a gender bias towards females in the online community similar to that found in some existing volunteer groups (Cherry, 2018; Domroese & Johnson, 2017). However, gender in existing groups varies according to factors such as the type (Cooper & Smith, 2010) and complexity (Davis et al., 2019) of the projects.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Bushway et al (2011) found younger people who were employed and on lower incomes were more likely to cite time and money as barriers, whereas retirees were the least likely. Our study found a gender bias towards females in the online community similar to that found in some existing volunteer groups (Cherry, 2018; Domroese & Johnson, 2017). However, gender in existing groups varies according to factors such as the type (Cooper & Smith, 2010) and complexity (Davis et al., 2019) of the projects.…”
Section: Discussionsupporting
confidence: 86%
“…The NatureVolunteers demographic (largely aged between 25–34 and female) differs greatly from those sampled in previous literature on improving participation in environmental projects. The contrast in age range between the NatureVolunteers online community and existing volunteers is particularly marked given that most research of current volunteers has found the age distribution to be much older (Asah & Blahna, 2013; Cherry, 2018; Davis et al., 2019; Domroese & Johnson, 2017). The lack of representation of younger people in environmental volunteering could be due to both a lack of awareness of projects and barriers to participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diane is one of many birders I interviewed who participate in a wide variety of environmental activism efforts, but who do not consider themselves to be environmental activists. Birding has long been associated with environmental activism, from its origins as a scientific hobby in the nineteenth century to today’s citizen scientist birders, whose counts demonstrate how birds’ ranges continue to move further northward due to anthropogenic climate change (Cherry 2018). Because of its size, strength, and longstanding efforts for environmental and wildlife protection, the National Audubon Society is now one of the “group of ten” mainstream environmental organizations in the United States (Rowell 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Clive added that having a professional researcher on board was important for helping the citizen scientists understand 'the regulations' as they began to undertake more sophisticated techniques, which posed greater risks to birds and therefore required further regulatory oversight. In short, citizen scientists are sometimes sceptical about their own abilities, 31 at least when it comes to data analysis and understanding regulations. This means that it is not just professionals who engage in 'demarcation work' by maintaining and reinforcing separation between professionals and volunteers, 32 but also non-professionals.…”
Section: Citizen Scientists and Aspa Licensingmentioning
confidence: 99%